Na4‐αM2+α/2(P2O7)2 (2/3 ≤ α ≤ 7/8, M = Fe, Fe0.5Mn0.5, Mn): A Promising Sodium Ion Cathode for Na‐ion Batteries. Issue 6 (18th February 2013) - Ha, Kwang‐Ho; Woo, Seung Hee; Mok, Duckgyun; Choi, Nam‐Soon; Park, Yuwon; Oh, Seung M.; Kim, Youngshol; Kim, Jeongsoo; Lee, Junesoo; Nazar, Linda F.; Lee, Kyu Tae
Abstract A new polyanion‐based compound, Na3.12M2.44(P2O7)2 (M = Fe, Fe0.5Mn0.5, Mn) is synthesized and examined as a cathode for Na ion batteries. Off‐stoichiometric synthesis induces the formation of a Na‐rich phase, Na3.32Fe2.34(P2O7)2 ‐ a member of the solid solution series Na4‐αFe2+α/2(P2O7)2 (2/3 ≤ α ≤ 7/8) ‐ which delivers a reversible capacity of about 85 mA h g−1 at ca. 3 V vs. Na/Na+ and exhibits very stable cycle performance. Above all, it shows fast kinetics for Na ions, delivering an almost constant 72% reversible capacity at rates between C/10 and 10C without the necessity for nanosizing or carbon coating. We attribute this to the spacious channel size along the a‐axis, along with a single phase transformation upon de/sodiation.